The acid house - Welsh, Irvine (Norton, 1998)
The characters in this extraordinary book are often - on the surface - depraved, vicious, cowardly and manipulative, but their essential humanity is never undermined. Two professors of philosophy turn pugilists; Leith removal men become the objects of desire for Hollywood goddesses; God turns Boab Coyle into a house-fly; and in the novella, 'A Smart Cunt', the drug-addled young hero spins off on a collision course with his past. The Acid House is a bizarre, disturbing and hilarious collection from one of the most uncompromising and original writers around.